2010
DOI: 10.1136/qshc.2008.030734
|View full text |Cite
|
Sign up to set email alerts
|

The impact of shift patterns on junior doctors' perceptions of fatigue, training, work/life balance and the role of social support

Abstract: BackgroundThe organisation of junior doctors' work hours has been radically altered following the partial implementation of the European Working Time Directive. Poorly designed shift schedules cause excessive disruption to shift workers' circadian rhythms.MethodInterviews and focus groups were used to explore perceptions among junior doctors and hospital managers regarding the impact of the European Working Time Directive on patient care and doctors' well-being.ResultsFour main themes were identified. Under “D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
49
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 17 publications
0
49
0
Order By: Relevance
“…One of the key aims of the new worktime arrangements was to reduce excessive fatigue among junior doctors, thereby enhancing patient safety and doctors' own well-being. However, the implementation of the EWTD has not led to an improvement in the situation in all cases, with highly demanding, yet EWTD-compliant work schedules commonly reported by junior doctors (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the key aims of the new worktime arrangements was to reduce excessive fatigue among junior doctors, thereby enhancing patient safety and doctors' own well-being. However, the implementation of the EWTD has not led to an improvement in the situation in all cases, with highly demanding, yet EWTD-compliant work schedules commonly reported by junior doctors (4).…”
mentioning
confidence: 99%
“…We sought to determine the impact of particular aspects of shift system design on four dependent variables: fatigue, sleep duration, psychological strain, and work-life interference. The schedule features to be examined were identified from a series of interviews and focus groups involving junior doctors and hospital managers [reported elsewhere (4)] and from a review of the relevant literature on shift work. The schedule features identified for examination were: (i) the number of night shifts worked consecutively, (ii) the length of night shifts, (iii) the number of scheduled rest days following a block of night shifts, (iv) the number of consecutive shifts (of any sort) worked without a break, (v) the frequency of weekends on-call, (vi) the frequency of daytime on-call shifts (Monday to Friday), (vii) the length of daytime on-call shifts, (viii) shorter intervals between the end of one shift and the start of the next ("quick returns"), (ix) and the number of hours worked per week.…”
mentioning
confidence: 99%
“…Performing the same amount of work in fewer hours (work compression) is of concern regarding workload44 and overall well-being,45 and may place trainee doctors at risk of burnout 46. Although much of the literature relating to fatigue comes from the USA where restricted working hours are still much longer than in Europe (eg, 80 h/week and longer maximum shift lengths), two UK self-report studies conducted shortly after implementation of the 48 h working week have highlighted the effect of different schedules on fatigue, including the negative effect of working 7 consecutive nights, having only 1 day of rest after night shifts, intervals of less than 10 h between shifts, and shifts of 12 consecutive days 30 31. Difficulty achieving naps during night shifts, and poor provision for naps, has been reported elsewhere 33.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced working hours have, however, not led to differences in the quality of patient care nor improved patient safety . In contrast, alteration of junior doctors' work hours has created different shift durations and work patterns, such as working seven consecutive nights, and then having large blocks of time rostered off work, which are not dissimilar to those in Australia . Unfortunately, this type of work leads to an accumulation of fatigue, and affects training opportunities in terms of consultant ward rounds, mentorship, tutorials and other in‐hospital education and has a negative impact on work/life balance …”
mentioning
confidence: 99%
“…3,4 In contrast, alteration of junior doctors' work hours has created different shift durations and work patterns, such as working seven consecutive nights, and then having large blocks of time rostered off work, which are not dissimilar to those in Australia. 16 Unfortunately, this type of work leads to an accumulation of fatigue, and affects training opportunities in terms of consultant ward rounds, mentorship, tutorials and other in-hospital education and has a negative impact on work/life balance. 16 A survey of doctors in the United Kingdom on their perceptions regarding the UK Working Time Regulations found that while these regulations have improved prolonged excessive working hours, they have not overcome fatigue and other negative consequences.…”
mentioning
confidence: 99%